Perbandingan Percutaneous Nephrolithotomy (PCNL) dan Open Nephorlithotomy Pada Pasien dengan Batu Staghorn : Systematic Review - Ramadhan, Ilham; Wibisono, Wibisono (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Introduction: Staghorn stones are one of the most severe forms of urinary lithiasis. They have a nuclear body and at least one calyceal branch. Untreated staghorn stones are associated with recurrent infections, stone growth, significant morbidity, and progressive loss of renal function. This requires further development of appropriate management, both open surgical and endourological. Objective: to compare percutaneous nephrolithotomy (PCNL) and open nephrolithotomy in patients with staghorn stones. Methods: This review was conducted in accordance with the requirements outlined in PRISMA 2020. A systematic search for studies to be included in the review was conducted from 20 February 2025 using GoogleScholar, PubMed and SagePub databases using the words: "percutaneous nephrolithotomy", "open nephrolithotomy", and "staghorn". Results: We found six studies comparing PCNL and open stone removal procedures between 2021 and 2025. All of these studies were obtained from Asian countries, one of which was Indonesia. Conclusion: Both open surgery and PCNL are effective options. Although, patients with PCNL generally have a shorter hospital stay, postoperative complications are lower in the open surgery group.